Perspectives of Faculty and Medical Students on Online Education during Coronavirus Disease 2019 Pandemic at a Medical College in Saudi Arabia - Jwaher A. Almulhem; Samar Binkheder; Alsaif Faisal Fahad; Aldgram Abdulaziz; Alomran Sulaiman; N. Aldekhyyel Raniah; Neel Khalid Fouda; Albarrak Ahmed; Mona M. Soliman (Wolters Kluwer Medknow Publications, 2024)
Background Medical education was affected worldwide by the coronavirus disease 2019 (COVID-19) pandemic. The sudden announcement of the lockdown resulted in a sudden, unplanned shift to online education. The study aimed to explore the perceptions of the faculty and medical students regarding the experience of utilizing online education at the College of Medicine (CoM), King Saud University, Saudi Arabia. Methods A cross-sectional study was conducted in 2022 with the faculty and medical students in the CoM, King Saud University. The students' survey was distributed using Google Forms. The questionnaire consisted of six sections with a total of 28 questions that included closed-ended, 5-point Likert scale, and binary "yes" and "no" questions: (1) demographic data, (2) using online education before COVID-19, (3) using of online education during COVID-19, (4) student perceptions of E-learning during COVID-19 pandemic, (5) impact of online education on clinical teaching, and (6) preference in future. The faculty survey was distributed electronically by E-mail through the university's official E-mail. The faculty survey consisted of 17 questions divided into "Demographic Information" and "Experience with E-Learning before and after COVID-19." Results A total of 302 students responded to the survey, with most being from year 4 (30%). Students spent more than 10 h using online learning platforms during the pandemic, compared with 1-3 h before the pandemic. The most used online learning resource indicated by students was YouTube (75%), with Zoom being the most preferred platform (48%). The main benefit of online teaching based on students' responses was that it saves students' time (88%), while lack of contact with teachers (43%) was a barrier. 76.2% of students indicated satisfaction with the online learning experience during COVID-19. Male students showed more satisfaction than females with the learning experience during COVID-19 (P = 0.029). Almost all students (90%) wanted to continue with online learning post-COVID-19. For the faculty survey, 61 faculty members completed the survey. Overall, the faculty positively viewed online teaching and e-learning interactions. About 39.4% identified giving both live and recorded sessions during COVID-19. About 65.57% of faculty used Zoom to conduct sessions. Regarding preference, 34% preferred e-learning compared to an actual classroom setup for theoretical lectures, and 33% preferred e-learning for problem-based learning lectures. Almost half of the faculty rated their experience as poor for clinical and practical sessions. For problem-based lectures, 34% of faculty rated their interaction with students as poor during online learning compared to the actual classroom. Conclusions Despite the challenges, medical students and faculty perceived the sudden shift to online education due to COVID-19 as satisfactory. However, further efforts are needed to improve the utilization and implementation of online education in medical education and regularly monitor its effectiveness.